Linking humanitarian response with resilience building in the drylands of the Horn of Africa - Mohamed, Tahira Shariff (International Livestock Research Institute, 2025)
'Lightning talk' presented by Tahira Mohamed (ILRI) at the Jameel Observatory Community of Practice meeting, Addis Ababa, 13-14 May 2025